STUDI PUNGLI DI TERMINAL, STASIUN KERETA API, DAN PELABUHAN UDARA DI KOTA BANDUNG - Siti Kusumawati Azhari (Fakultas Seni Rupa dan Desain ITB, 2008)
Terminal is one of the places where illegal retribution frequently takes place. One kind of illegal retribution os often experienced by bus drives or drives of other public transportation vehicles. The drives have to pay for this illegal retribution on top of the legal retribution. This illegal retribution is often collected by amember of an organization and a member of a gang. This action not only causes a loss to the nation's revenue but also violetes the people's social and economic rights. Thus, this action can be categorized as corruption (criminal act) and results in high cost for both the passengers of airplane and train, and therefore has to be eradicated. In relation with the above-mentioned fact, this study wa conducted to know further about this criminal act, which takes place both in Bandung city's airport and railway stations. The method used in this study was qualitative one, in which some direct observation and interviews were carried out. In addition, photographing and video shooting were also done. It was found that not only the bus drivers and other public transportation drivers who were affected by this illegal retribution, but also were the sellers and both the passengers of airplane and train. They could not refuse to pay the illegal retribution since they were threatened by the illegal retribution collectors. It was also found the the illegal collectors include the officials of the airport and railways, members of an organization and member of a gang